The element of mysticism in the selected works of Kahlil Gibran - Altabaa, Homam (Kulliyyah if Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
This study takes a comparative and analytical approach to exploring the various mystical aspects that encompass selected creative works of Kahlil Gibran in English and Arabic. It presents an overview of theistic mysticism as the guiding light for the analysis of his works, before examining the mystical themes represented by Gibran such as Truth, the Perfect Divine Being, the mystic path, and spiritual morality, coupled with analogies from Islamic and Christian mysticism. The study finds that Gibran adopts mysticism as a universal answer to questions about the meaning of life and as a path that seeks to elevate man above material preoccupations into a world of spiritual and moral perfection. Gibran uses a prophetic voice to guide the soul from its transcendental origin through a journey of purification, gnosis, and love to reach mystical unity with God. It highlights that the importance of the mystical element cannot be overestimated in the works of Gibran. The mystical element is the link that unifies his Arabic and English works, and propels them to enduring literary and popular success across cultures. He places himself as a writer in the traditional context of mysticism, taking the esoteric heart and spiritual core of all religions to be one. The moral values promoted by Gibran are based on his mystical outlook and his conception of a just and loving God.